2021
DOI: 10.3389/fcell.2021.755740
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution 3D Reconstruction of Human Oocytes Using Focused Ion Beam Scanning Electron Microscopy

Abstract: The egg plays a pivotal role in the reproduction of our species. Nevertheless, its fundamental biology remains elusive. Transmission electron microscopy is traditionally used to inspect the ultrastructure of female gametes. However, two-dimensional micrographs contain only fragmentary information about the spatial organization of the complex oocyte cytoplasm. Here, we employed the Focused Ion Beam Scanning Electron Microscopy (FIB-SEM) to explore human oocyte intracellular morphology in three dimensions (3D). … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…However, no studies tackled to address molecular mechanisms underlying the emergence of different cytoplasmic irregularities in developing human oocytes. We have previously mapped out ultrastructural changes during human oocyte maturation, and our 2D and 3D image data documented major reorganization of ooplasm in preparation for fertilization (23,24). Correct positioning and active movement of organelles within the cytoplasm rely on their interaction with cytoskeleton components.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…However, no studies tackled to address molecular mechanisms underlying the emergence of different cytoplasmic irregularities in developing human oocytes. We have previously mapped out ultrastructural changes during human oocyte maturation, and our 2D and 3D image data documented major reorganization of ooplasm in preparation for fertilization (23,24). Correct positioning and active movement of organelles within the cytoplasm rely on their interaction with cytoskeleton components.…”
Section: Introductionmentioning
confidence: 79%
“…High magnification is needed to detect pathological features such as misshaped mitochondria and enlarged SER. The development of high-resolution tomographic methods now enables volumetric imaging of oocyte and ovarian tissue architecture (24,53). Three-dimensional reconstruction of isolated and/or cumulusenclosed dysmorphic oocytes would elucidate the spatial relationship of subcellular structures and advance our understanding of how the oocytes interact with surrounding cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heymann et al [ 133 ] first reported the 3D volume reconstruction of biological specimens for yeast cells. Trebichalská et al [ 134 ] reconstructed an unprecedented view of ooplasmic architecture and observed organelle distribution patterns in nine donor oocytes’ developmental competence. 3D image segmentation was performed to extract information.…”
Section: 3d Controllable Fabrication Of Nanomaterials With Fib-semmentioning
confidence: 99%